Affective startle potentiation differentiates primary and secondary variants of juvenile psychopathy. (29th December 2016) - Kimonis, Eva R.; Fanti, Kostas A.; Goulter, Natalie; Hall, Jason
Abstract: Individuals with psychopathic traits show an attenuated emotional response to aversive stimuli. However, recent evidence suggests heterogeneity in emotional reactivity among individuals with psychopathic or callous–unemotional (CU) traits in the identification of primary and secondary subtypes, or variants. We hypothesized that primary CU variants will respond with blunted affect to negatively valenced stimuli, whereas individuals with a history of childhood maltreatment, fitting with theoretical conceptualizations of secondary psychopathy, will display heightened emotional reactivity. To test this hypothesis, we examined fear-potentiated startle between CU variants while viewing aversive, pleasant, and neutral scenes. Two hundred thirty-eight incarcerated adolescent ( M age = 16.8 years, SD = 1.11 years) boys completed a picture-startle paradigm and self-report questionnaires assessing CU traits, aggressive behavior, and maltreatment. Latent profile analysis of CU trait, aggression, and maltreatment scores identified four classes: primary psychopathy variants (high CU traits, high aggression, low maltreatment; n = 46), secondary psychopathy variants (high CU traits, high aggression, high maltreatment; n = 42), and two nonpsychopathic groups differentiated on maltreatment experience ( n = 148). Primary CU variants displayed reduced startle potentiation to aversive images relative to control, maltreated, and also secondary variants that exhibited greater startle modulation. Findings add to a rapidly growing body of literature supporting the possibility of multiple developmental pathways to psychopathic traits (i.e., equifinality), and extend it by finding support for divergent potential biomarkers between primary and secondary CU variants.